Comparison of the Polar V800 and the Garmin Forerunner 230 to Predict V[Combining Dot Above]O2max. Issue 5 (May 2021) - Snyder, Nikolas C.; Willoughby, Courtney A.; Smith, Bryan K.
Abstract : Abstract: Snyder, NC, Willoughby, CA, and Smith, BK. Comparison of the Polar V800 and the Garmin Forerunner 230 to predict V[Combining Dot Above]O2 max. J Strength Cond Res 35(5): 1403–1409, 2021—The purpose of this study was to compare maximal oxygen consumption (V[Combining Dot Above]O2 max) values (Amax ) with predicted V[Combining Dot Above]O2 max values obtained from the Polar V800 (PV800) and the Garmin Forerunner 230 (GF230) to determine whether the accuracy of these estimates differs between sexes. The PV800 predicts V[Combining Dot Above]O2 max based on resting heart rate (HR). The GF230 predicts V[Combining Dot Above]O2 max based on a 10-minute, self-paced outdoor run. Subjects consisted of 22 women and 22 men. After a 10-minute supine rest, predicted V[Combining Dot Above]O2 max (Pmax ) values from the PV800 were measured during a 5-minute supine rest. Subjects then completed a treadmill V[Combining Dot Above]O2 max test to determine Amax . Within 48 hours of obtaining Amax, individuals completed a 10-minute, self-paced outdoor run using the GF230 to predict V[Combining Dot Above]O2 max (Gmax ). A 2-way (watch vs. sex) analysis of variance was used to determine whether there were differences between predicted V[Combining Dot Above]O2 max and Amax between sexes. A significant interaction between HR monitors and sex was found ( p = 0.007). Follow-up analysis showed that in men, Pmax was significantly overestimated compared with Gmax (3.87 ± 1.53 ml·kg −1 ·min −1, p = 0.013). Bland-Altman plots revealed large random errors that ranged from 6.6 to 16.4 ml·kg −1 ·min −1 with the PV800 having larger errors than the GF230. The results of this study indicate that the GF230 can provide an accurate estimate of V[Combining Dot Above]O2 max in both sexes. The PV800 can provide an accurate estimate of V[Combining Dot Above]O2 max for women but not men. Estimates of V[Combining Dot Above]O2 max from the both devices should be used with caution because of the large random error associated with them.